2013
DOI: 10.1002/dvg.22384
|View full text |Cite
|
Sign up to set email alerts
|

Non‐parallel recombination limits cre‐loxP‐based reporters as precise indicators of conditional genetic manipulation

Abstract: Cre/LoxP-mediated recombination allows for conditional gene activation or inactivation. When combined with an independent lineage-tracing reporter allele, this technique traces the lineage of presumptive genetically modified Cre-expressing cells. Several studies have suggested that floxed alleles have differential sensitivities to Cre-mediated recombination, which raises concerns regarding utilization of common Cre-reporters to monitor recombination of other floxed loci of interest. Here, we directly investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 30 publications
8
89
0
1
Order By: Relevance
“…However, we observed that efficiency of recombination in pericytes using this reporter was less than that observed using the td-Tomato reporter, in this case 41.94 ± 18.67 % (n=5) of NG2 + cells were GFP + . Discrepancies between recombination efficiency in different mouse reporter lines (including Rosa-tdTomato and Rosa-mT/mG ) have already been described by Liu et al [19], and the differences we observed in efficiency are similar to what has been previously noted. Liu et al proposed that their results imply that reporter sensitivity inversely correlates with the distance between the LoxP sites, a theory that is consistent with previous observations by Coppoolse et al [20].…”
Section: Resultssupporting
confidence: 90%
“…However, we observed that efficiency of recombination in pericytes using this reporter was less than that observed using the td-Tomato reporter, in this case 41.94 ± 18.67 % (n=5) of NG2 + cells were GFP + . Discrepancies between recombination efficiency in different mouse reporter lines (including Rosa-tdTomato and Rosa-mT/mG ) have already been described by Liu et al [19], and the differences we observed in efficiency are similar to what has been previously noted. Liu et al proposed that their results imply that reporter sensitivity inversely correlates with the distance between the LoxP sites, a theory that is consistent with previous observations by Coppoolse et al [20].…”
Section: Resultssupporting
confidence: 90%
“…S8). It was reported that non-parallel recombination exists between R26R reporter and targeted gene deletion, and the differences in the chromosomal location, the distance spanning LoxP sites, the sequences around the LoxP sites and the level of Cre activity in the cells probably contribute to the non-parallel recombination (Liu et al, 2013). In our hand, Six3-deletion and β-gal reporter expression are mostly exclusive and we did not see complete Six3-deletion in E8.5 Six3 mutant embryos in which drastic phenotypes were obvious, no matter Six3 -deletion was driven by Six3-Cre (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different CreER strains may exhibit highly variable sensitivity to tamoxifen-induced reporter expression, depending on the strength of the Cre-driving promoter and the respective reporter strain used (34). Further, the possibility of tamoxifen-independent reporter expression as well as de novo recombination events caused potentially by tamoxifen that was not eliminated during injury must be considered.…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%